Effectiveness and safety of lenvatinib in a series of advanced well-differentiated thyroid carcinomas from a single tertiary cancer center and literature review - Damásio, Inês L (2024)
BACKGROUND: Treatment of advanced differentiated thyroid carcinoma (DTC) remains a challenge as 25-50% of patients with locally invasive or distant metastatic disease become refractory to radioiodine (RAI) therapy. Tyrosine kinase inhibitors (TKI) are increasingly used in this setting. The SELECT trial demonstrated that lenvatinib, a multikinase inhibitor, significantly improved progression free survival (PFS) compared to placebo. Our aim was to report the effectiveness and safety of lenvatinib in our series of patients with advanced DTC. METHODS: A total of 25 patients with advanced DTC followed at a single tertiary center from January of 2016 to January of 2022 were retrospectively reviewed. RESULTS: Patients were treated with a mean daily dose of lenvatinib of 16.9 mg for a mean of 9.1 months. Median estimated PFS was 31.3 months. One patient achieved complete response. The objective response rate (ORR) was 40% and the disease control rate was 84%. The mean change in summed longest diameter of target lesions from baseline to nadir was -36.9%. Lenvatinib prolonged the tumor volume doubling time in 86.7% patients. Interestingly, we found that patients treated with a lower dose of lenvatinib (<16.9 mg daily) had a significantly higher PFS and ORR than patients treated with higher dosages (>16.9 mg). Adverse events were frequently reported. CONCLUSIONS: Our results confirm the effectiveness of lenvatinib in the management of patients with advanced DTC and support the need to adjust the dosage of lenvatinib to patient´s performance status and comorbidities.